2020
DOI: 10.1007/s11104-020-04533-0
|View full text |Cite
|
Sign up to set email alerts
|

Plant defense responses in monocotyledonous and dicotyledonous host plants during root-knot nematode infection

Abstract: Background Root-knot nematodes (RKNs)-Meloidogyne spp.are a group of nematodes distributed worldwide that infect monocotyledonous and dicotyledonous crop species. Plant responses to RKNs have been described in many studies of various host plants. In the course of parasitism, RKNs induce the transcriptional reprogramming of host cells to establish giant cells. Nematode attack induces many mechanisms in host plants, including pathogen-associated molecular pattern (PAMP)-triggered immunity (PTI) and effectortrigg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(15 citation statements)
references
References 102 publications
1
13
0
1
Order By: Relevance
“…Besides, we imply ABA has a potential role in Gpa2 functioning. This evidence is in line with the well-reported role of the above signaling in plant defense responses against various pathogens (Koornneef and Pieterse, 2008;Ali et al, 2018;Przybylska and Obrępalska-Stęplowska, 2020;Sun and Zhang, 2021); however, different from H1/Hero A transcriptome studies, which are all based on data comparison between the resistant and susceptible cultivars. We only infected resistant potato roots with a Gpa2-virulent population and an avirulent population of G. pallida.…”
Section: Downstream Signaling Involved In R Genes-mediated Resistance...supporting
confidence: 76%
“…Besides, we imply ABA has a potential role in Gpa2 functioning. This evidence is in line with the well-reported role of the above signaling in plant defense responses against various pathogens (Koornneef and Pieterse, 2008;Ali et al, 2018;Przybylska and Obrępalska-Stęplowska, 2020;Sun and Zhang, 2021); however, different from H1/Hero A transcriptome studies, which are all based on data comparison between the resistant and susceptible cultivars. We only infected resistant potato roots with a Gpa2-virulent population and an avirulent population of G. pallida.…”
Section: Downstream Signaling Involved In R Genes-mediated Resistance...supporting
confidence: 76%
“…Examples include modulation of meristem determinacy [61] and stomatal guard cell density [48]. Several works have similarly highlighted diverse molecular responses to pathogen attack (for reviews, see [62][63][64]). Viewed holistically, genetic control of trait plasticity is clearly complex (see, e.g., [65])…”
Section: Measuring Active Adaptive Plasticitymentioning
confidence: 99%
“…Many studies of nematode resistance have indicated the action of few genes with greater effect (Passianotto, et al, 2017;Mota, et al, 2020). There are also other results, that indicate the action of lesser effect genes that have evolved over time, according to the gene-for-gene theory (Bell et al, 2019;Przybylska;Obrępalska-Stęplowska, 2020). In C. canephora, the plant-pathogen response mechanism is related to a hypersensitivity response, which occurs shortly after root penetration and establishment of a feeding site, starting an attack and defense gene interaction between pathogen and host (Lima et al, 2015;Maghuly;Jankowicz-Cieslak;Bado, 2020).…”
Section: Resultsmentioning
confidence: 99%